2007
DOI: 10.1002/mnfr.200700064
|View full text |Cite
|
Sign up to set email alerts
|

The atherosclerotic heart disease and protecting properties of garlic: contemporary data

Abstract: This article reviews the contemporary data concerning atherosclerosis and protecting properties of garlic. Recent advances in basic science have established a fundamental role for inflammation in mediating all stages of this disease from initiation through progression and, ultimately, the thrombotic complications of atherosclerosis. These new findings provide important links between risk factors and the mechanisms of atherogenesis and garlic properties. Numerous in vitro studies have confirmed the ability of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 123 publications
(147 reference statements)
2
36
0
Order By: Relevance
“…17,18 Previous studies have shown that raw garlic has profoundly decreases TC and TG levels without changing high-density lipoprotein cholesterol levels in rats fed HCD, whereas boiled garlic has little effect on these parameters. 19,20 In a human study, 21 supplementation with raw garlic, powdered garlic, or aged garlic extract (4 g/day) for 6 months significantly lowered LDL-C and other plasma lipid levels in adults with moderate hypercholesterolemia. Our findings in rats provide further support for the antihyperlipidemic, antihypercholesterolemic, and anti-atherosclerotic actions of processed garlic products because both crushed raw garlic and high temperature/high pressure-processed garlic exhibited remarkable antihyperlipidemic action by decreasing the levels of TG, LDL-C, and TC in plasma and increasing the levels of TG and TC in feces.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Previous studies have shown that raw garlic has profoundly decreases TC and TG levels without changing high-density lipoprotein cholesterol levels in rats fed HCD, whereas boiled garlic has little effect on these parameters. 19,20 In a human study, 21 supplementation with raw garlic, powdered garlic, or aged garlic extract (4 g/day) for 6 months significantly lowered LDL-C and other plasma lipid levels in adults with moderate hypercholesterolemia. Our findings in rats provide further support for the antihyperlipidemic, antihypercholesterolemic, and anti-atherosclerotic actions of processed garlic products because both crushed raw garlic and high temperature/high pressure-processed garlic exhibited remarkable antihyperlipidemic action by decreasing the levels of TG, LDL-C, and TC in plasma and increasing the levels of TG and TC in feces.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocystein should be considered as a risk factor for cardiovascular diseases in humans [4,18].…”
Section: Discussionmentioning
confidence: 99%
“…Garlic is well known powerful anti-atherogenic supplement [20]. Many reports have evaluated the effectiveness of garlic extracts/bioactive components in protection against CVD.…”
Section: Effects Of Garlic On Cardiovascular and Cerebrovascular Disementioning
confidence: 99%